PROBLEMS OF DEVELOPING STUDENTS' COMMUNICATIVE COMPETENCE - Khamdam-Zoda Leyla Khasanovna (Social science and innovation, 2024)
This article is devoted to the issue of students' communicative needs and the problem of forming students' linguistic competence. The communicative methodology is a pattern that is in demand in modern educational conditions, where the learning process is a model of the communication process. Knowledge of the communicative needs of students allows you to more accurately imagine what the description of language material in a practical Russian language course should be, how it should be selected, presented and mastered in a communicative-oriented learning environment.